INTERCULTURAL COMMUNICATION IN POETIC WORKS OF NIKOLAI ILYIN - Шукурова Л. Р. (Bright Mind Publishing, 2025)
The work of N. D. Ilyin opens new horizons for the perception and understanding of various cultures through artistic expression. The interaction between Russian and Uzbek literary traditions emphasizes the importance of intercultural dialogue and contributes to the expansion of literary interests, which, in turn, enriches both Russian and Uzbek literature. Thus, the study of Ilyin's work becomes particularly relevant. His writings serve as a connecting link between Russian and Uzbek literature. Analyzing Ilyin's works in the context of intercultural communication is a necessary step for understanding the cultural exchange between the Russian and Uzbek languages, as well as for deepening mutual understanding between the two literary traditions.
Keywords: Culture, dialogue, tradition, nature, translations, original works, poetry, society.